2019
DOI: 10.1002/pon.5189
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to cognitive problems reported by breast cancer survivors seeking cognitive rehabilitation: A qualitative study

Abstract: Objective: Qualitative studies have elucidated cancer survivors' experiences of cognitive changes associated with cancer and cancer treatment. This study specifically explored experiences of women treated for breast cancer who were seeking cognitive rehabilitation. The objective was to characterise the frequency and nature of cognitive changes and adaptations to cognitive change reported by these participants to better understand treatment needs of this group.Method: Australian women who had completed primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A recent systematic review of self-reported CRCI measures noted that this research has predominantly but not exclusively involved women with breast cancer, and that such self-report measures tend to show moderate to strong relationships with other patient-reported outcomes but weak or absent associations with neuropsychological tests (Bray et al, 2018). People affected by CRCI have emphasised its impact on quality of life (Tannock et al, 2004) due to limitations in activities such as work performance (Boykoff et al, 2009;Myers, 2013;Von Ah et al, 2013;Wagner et al, 2009), and family and social life (Green et al, 2019). Many researchers have found increases in selfreported CRCI to associate with increased psychological distress and fatigue (King & Green, 2015;Lai et al, 2009;Vardy & Dhillon, 2017); these bidirectional relationships indicate that it is important to consider broader function, such as emotional and physical wellbeing, in addition to neurological functioning (Costa et al, 2018;Green et al, 2005;Skaali et al, 2011).…”
mentioning
confidence: 91%
“…A recent systematic review of self-reported CRCI measures noted that this research has predominantly but not exclusively involved women with breast cancer, and that such self-report measures tend to show moderate to strong relationships with other patient-reported outcomes but weak or absent associations with neuropsychological tests (Bray et al, 2018). People affected by CRCI have emphasised its impact on quality of life (Tannock et al, 2004) due to limitations in activities such as work performance (Boykoff et al, 2009;Myers, 2013;Von Ah et al, 2013;Wagner et al, 2009), and family and social life (Green et al, 2019). Many researchers have found increases in selfreported CRCI to associate with increased psychological distress and fatigue (King & Green, 2015;Lai et al, 2009;Vardy & Dhillon, 2017); these bidirectional relationships indicate that it is important to consider broader function, such as emotional and physical wellbeing, in addition to neurological functioning (Costa et al, 2018;Green et al, 2005;Skaali et al, 2011).…”
mentioning
confidence: 91%
“…Qualitative methods have been used, mostly with breast cancer patients, to investigate CRCI complaints or speci c contexts such as work performance, symptom impacts on the patient's life, patients' own strategies, and supportive care needs for symptom management [13][14][15]. Pergolizzi stressed that simply asking the patient about perceived cognitive changes might be a stepping stone to nding nonpharmacological ways to address cognitive impairment [13].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative methods were utilized by several researchers mostly in breast cancer patients, to deeply explore CRCI complaints or speci c contexts such as work performance, symptom impacts on the patients' life, patients' own strategies and supportive care needs for symptom management [14][15][16] . As Pergolizzi emphasized that simply asking the patient about their perceived cognitive changes might be stepping stone to nding non-pharmacological ways to address cognitive impairment 14 .…”
Section: Introductionsmentioning
confidence: 99%